Disseminated Tularemia: Finding the Needle in the Haystack. (14th June 2020) - Stringham, Sean; Green Hines, Andrea; Attebery, Jonah; Darwin, Lisa; Wachholtz, Abby; Deschamp, Ashley; Choudhry, Ojasvini; Neemann, Kari
Abstract: We report a case of disseminated tularemia in a previously healthy 8-month-old male. This case highlights an atypical presentation of tularemia with multisystem organ involvement. The diagnosis was complicated by concurrent primary cytomegalovirus infection. Bronchoalveolar lavage culture confirmed the diagnosis. The patient was successfully treated with gentamicin. Pertinent literature reviewed.